2005
DOI: 10.1111/j.1751-0813.2005.tb13341.x
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity and specificity of single manual examination tests for detection of corpora lutea in the ovaries of non-cycling cows

Abstract: Errors associated with pre-mating heat detection are likely to result in between 15 to 30% of cycling cows not detected in oestrous before mating, resulting in the inclusion of cycling cows within the population of non-cycling cows. This mixed population of cows is then subjected to manual examination by veterinarians in order to assign cows to treatment groups. The corpus luteum test has modest sensitivity and high specificity and the size test has high sensitivity and low specificity. Therefore the use of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Our results came in agreement with that reported by others (Földi et al, 2006;Palmer, 2008) who found that, diagnosis of clinical endometritis using rectal palpation is subjective, not effective and prone to error as it lacks standardization. In the same manner, it had been reported that, transrectal palpation to identify the presence of a CL is imperfect (Shephard, 2005;Bicalho et al, 2008), but generally has a high specificity and is a "useful tool" that is widely used in veterinary practice. The good fertility results obtained in this study after using US as a diagnostic tool were corresponded to others (Kasimanickam et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our results came in agreement with that reported by others (Földi et al, 2006;Palmer, 2008) who found that, diagnosis of clinical endometritis using rectal palpation is subjective, not effective and prone to error as it lacks standardization. In the same manner, it had been reported that, transrectal palpation to identify the presence of a CL is imperfect (Shephard, 2005;Bicalho et al, 2008), but generally has a high specificity and is a "useful tool" that is widely used in veterinary practice. The good fertility results obtained in this study after using US as a diagnostic tool were corresponded to others (Kasimanickam et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, the US detection of intrauterine fluid was the unique feature for diagnosis of endometritis and this was supported by Kasimanickam et al (2004) who considered the presence of any US detectable uterine fluid as evidence of subclinical endometritis. In addition, use of US might increase the accuracy of identification of a CL (Shephard, 2005). On the contrary, Ghasemi (2011) reported that US measurements of both cervical diameter and endometrial thickness is not useful for detecting cows with endometritis.…”
Section: Discussionmentioning
confidence: 99%
“…That is, cows may fi rstly be defi ned as anoestrus based on lack of removal of tail paint or other oestrus-detection aids (Macmillan and Curnow 1977), and secondly by failure to detect a CL upon palpation or using another diagnostic test. Recently it has been suggested that a single palpation of the ovaries for the presence of a CL in anoestrous cows was not suffi ciently accurate to allow decisions to be made regarding treatment (Shephard 2005).…”
Section: Introductionmentioning
confidence: 99%